1078. Renal Transplant Recipient Resistomes Reveal Expansive Sub-Clinical Burden of Resistance After Treatment for ESBL-Producing Bacterial Infections. (31st December 2020) - Woodworth, Michael; Conrad, Roth; Strudwick, Amanda F; Babiker, Ahmed; Pouch, Stephanie M; Pouch, Stephanie M; Mehta, Aneesh; Friedman-Moraco, Rachel; Adelman, Max W; Konstantinidis, Kostas; Kraft, Colleen
Abstract: Background: Renal transplant recipients have frequent infection and colonization with antibiotic resistant (AR) bacteria. However, little is known about the burden of AR following targeted antibiotic treatment. Methods: This was a prospective study conducted as part of a single center clinical trial at Emory University. Demographic and clinical data regarding transplant and AR bacterial infection were abstracted. Stool samples were collected from renal transplant recipients treated with antibiotics for ESBL-producing gram negative infections. Bacterial cultures with AR-selective media and Illumina short-read sequencing were performed on stool samples. Confirmatory phenotypic isolate AR testing was performed with the Vitek2 platform. Resistome profiles were produced by assembling short reads into scaffolds using MetaSPAdes, predicting protein coding sequences using Prodigal and classifying proteins as antimicrobial resistance determinants using AMRFinderPlus. AMRFinderPlus results for patients were then compared to fecal metagenomes from 3 healthy Human Microbiome Project controls. Differences in AR genes in renal transplant patients vs controls were compared. Results: Metagenome sequencing was performed for 6 (5 female) patient stool samples. Stools were collected a median of 30 days after infection. The median number of AR genes per patient metagenome was 48.5 (range 23 to 87 genes). The median number of AR genes per control metagenome was 24 (range 16 to 25 genes). We detected 97 unique AR genes across all samples, 63 of which (65%) were detected in patient samples but not controls. All AR genes found in control metagenomes were present in at least one patient metagenome. No AR genes detected in patients were common to all patients. Subsets of clinically relevant genes corresponded with patient stool AR bacteria culture results. Antimicrobial resistance gene detection heatmap for renal transplant recipient stool samples after antibiotic treatment for ESBL infection. Conclusion: Viable AR bacteria and diverse AR gene profiles were frequently detected from renal transplant recipient stool samples after antibiotic treatment for infection. These data suggest that AR bacterial colonization and AR gene profiles may require distinct treatments other than systemic antibiotics for eradication. Disclosures: All Authors : No reported disclosures